Tissue metallothionein response in the Japanese quail associated with exposure to cyanobacterial biomass, lead and the Newcastle disease virus - Kovacova, Veronika; Piacek, Vladimir; Abdelsalam, Ehdaa Eltayeb Eltigani; Bandouchova, Hana; Heger, Tomas; Kobelkova, Katerina; Sedlackova, Jana; Vitula, Frantisek; Pikula, Jiri (Neuro-endocrinology letters, 2019)
OBJECTIVES: Here we tested the hypothesis that multiple toxic and infectious stressors combine in their adverse effects to produce higher tissue responses of metallothioneins (MTs) in birds. METHODS: We used Japanese quails as a model avian species. The study is based on data obtained from single and combined exposures of Japanese quails to cyanobacterial biomass containing microcystins, lead and a live Newcastle disease vaccination virus. Eight groups of 5 birds were exposed to single, double and triple combinations of these stressors and compared with controls. Birds were euthanized after the 30-day exposure to collect brain, liver, kidney, and pectoral muscle for MTs measurement. RESULTS: Baseline levels of MTs differed in avian tissues. The gradient of MTs in control quails was pectoral muscle < liver < brain < kidney. Double and triple exposures induced higher levels of MTs. While increases of MTs were driven mainly by dietary exposure to cyanobacterial biomass and/or lead, Newcastle disease vaccination induced the least response. Induction of brain MTs was dominated by exposure to lead. Patterns of MTs responses were similar in the liver and pectoral muscle as well as in the kidney and brain. CONCLUSIONS: Understanding better responses of birds to oxidative stress induced by toxic and infectious stressors may have implications for avian conservation issues and disease risk assessment.